2004
DOI: 10.1029/2003jf000034
|View full text |Cite
|
Sign up to set email alerts
|

Constraining climatic controls on hillslope dynamics using a coupled model for the transport of soil and tracers: Application to loess‐mantled hillslopes, South Island, New Zealand

Abstract: [1] Landscapes reflect a legacy of tectonic and climatic forcing as modulated by surface processes. Because the morphologic characteristics of landscapes often do not allow us to uniquely define the relative roles of tectonic deformation and climate, additional constraints are required to interpret and predict landscape dynamics. Here we describe a coupled model for the transport of soil and tracer particles at the hillslope scale. To illustrate the utility of this methodology, we modeled the evolution of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 58 publications
(71 reference statements)
5
47
0
Order By: Relevance
“…Such mass replacements do not occur for depositional soils or soils on level grounds. In addition, a number of studies have found evidence for transient behavior both in terms of geochemistry (e.g., Birkeland and Berry, 1991) and soil thickness (e.g., Birkeland and Berry, 1991;Roering et al, 2004;Roering and Gerber, 2005) on eroding hillslopes. Indeed, hillslopes' response to changes in climate and tectonics occurs at the timescales that are longer than the period of recent glacial and interglacial cycles (Fernandes and Dietrich, 1997;Roering et al, 2001;Mudd and Furbish, 2007).…”
Section: Background and Issuesmentioning
confidence: 98%
“…Such mass replacements do not occur for depositional soils or soils on level grounds. In addition, a number of studies have found evidence for transient behavior both in terms of geochemistry (e.g., Birkeland and Berry, 1991) and soil thickness (e.g., Birkeland and Berry, 1991;Roering et al, 2004;Roering and Gerber, 2005) on eroding hillslopes. Indeed, hillslopes' response to changes in climate and tectonics occurs at the timescales that are longer than the period of recent glacial and interglacial cycles (Fernandes and Dietrich, 1997;Roering et al, 2001;Mudd and Furbish, 2007).…”
Section: Background and Issuesmentioning
confidence: 98%
“…3) resemble those interpreted to be fecal pellets produced by soil invertebrates in other Chernozemic soils (Pawluk and Bal 1985). Physical processes may also be involved in modifying soil microstructure, as in the case of elongated aggregates transitional to platy microstructures similar to those attributed to frost action in southern British Columbia Chernozemic A horizons (Sanborn and Pawluk 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The parent material complexity exhibited by these pedons, most notably at the Carmacks site, would actually facilitate such research. Dated marker beds with distinctive compositions, such as the White River tephra, can be useful tracers in studies of soil mixing and transport on slopes (Roering et al 2004). In addition, the late Holocene resumption of loess deposition at Kluane Lake provides an unusual opportunity to examine the responses of soils in a grassland-forest mosaic to aeolian processes (Sanborn and Jull 2009).…”
Section: Discussionmentioning
confidence: 99%
“…They used the depth variation of a 27 ka tephra within the uppermost loess sheet along a slope transect from interfluve to gully floor. Subsequent simulations (Roering et al, 2004) adequately replicated the evolution of the paleohillslope (as revealed from loess stratigraphy) to the present convex form, and also the profile distribution and concentration of tephra along the transect. This model allows us to make predictions about loess preservation based on topographic variables and compare them with field observations.…”
Section: Study Area and Approachmentioning
confidence: 76%
“…What is that point, and what processes are involved? Roering et al (2002Roering et al ( , 2004 showed that erosion rates on the Dillondale terrace are determined by local curvature. Sediment flux rate, q s (m 3 m − 1 yr − 1 ) varies proportionally with hillslope gradient (in one dimension) as:…”
Section: Coupled Landform Geomorphic and Loess Mantle Evolution In Chmentioning
confidence: 99%